The Effect of estrogen hormone of the recovery of female with COVID-19 - Mafatihul Inayah; Titi Maharrani; Dina Isfentiani; Siti Mar’atus Sholikah; Zarinah Binti Abdul Aziz (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease that attacks the respiratory tract and it is known that the female sex shows a higher cure rate than men due to hormonal influences, namely the hormone estrogen. This research aims to conduct a systematic review of the results of the latest research on the effect of the hormone estrogen on the recovery of female with COVID-19. The article search found 1373 articles from 4 electronic databases, namely PubMed, Research Gate, Science Direct, and Google Scholar which were published in 2020-2021 using keywords and the boolean operator AND. Then the articles were selected using the PRISMA Flow Diagram instrument so that 11 articles were obtained that met the inclusion criteria. The eleven articles were then analyzed to assess the quality of the articles using The Joanna Briggs Institute (JBI) instrument. An article that deserves a review if it gets a score of more than 50%. After analyzing the assessment with JBI, 11 articles were declared eligible for review because them get a score of more than 50%. Seven of the 11 articles stated that the hormone estrogen had a significant effect on healing COVID-19, especially in female. Four other articles stated that the hormone estrogen had no significant effect on the recovery of women with COVID-19 due to several influencing factors including age, Body Mass Index (BMI), comorbid diseases, and smoking habits. The hormone estrogen affects the recovery of female with COVID-19 especially in young female, normal BMI, no comorbid, and not smoking. It is necessary to carry out a further literature review on the effect of the hormone estrogen on healing COVID-19 in female by taking into account the number of samples, sample criteria, and measurement of estrogen hormone levels.